GEOGRAPHY TEACHING MATERIAL DESIGN FOR MARINA BEACH TOURIST ATTRACTION IN SEMARANG THROUGH PHOTOGRAPHY ESSAY MEDIA - Amrullah, M Fikri; Budi Nur Sidiq, Wahid Akhsin; Wijayanti, Lina Adi (Universitas Negeri Makassar, 2025)
This study aims to design geography learning materials based on the tourism potential of Marina Beach in Semarang by utilising photography essay media. The background of this study stems from the importance of contextual learning in the Merdeka Curriculum, which emphasises the integration of local potential so that students are able to relate geographical concepts to real life. This study uses a descriptive-exploratory method with observation, interview, and photo documentation techniques. The results show that Marina Beach has great potential as a source of geography learning, covering physical, social, and economic aspects (the role of MSMEs and local tourism). Through photography essays, geographical phenomena are visualised in the form of a series of photos accompanied by narratives, thus connecting theoretical concepts with reality in the field. The resulting teaching material design can be integrated into contextual learning projects, improving students' spatial literacy, critical thinking skills, and ecological awareness.